Auxin Requirements of Sycamore Cells in Suspension Culture - Moloney, Maurice M. (1983)
Sycamore (Acer pseudoplatanus L.) cell suspension cultures (strain OS) require 2,4-dichlorophenoxyacetic acid (2,4-D) in their culture medium for normal growth. If the 2,4-D is omitted, rates of cell division are dramatically reduced and cell lysis may occur. Despite this `auxin requirement,' it has been shown by gas chromatography-mass spectrometry that the cells synthesize indol-3yl-acetic acid (IAA). Changes in free 2,4-D and IAA in the cells during a culture passage have been monitored. There is a rapid uptake of 2,4-D by the cells during the lag phase leading to a maximum concentration per cell (125 nanograms per 10(6) cells) on day 2 followed by a decline to 45 nanograms per 10(6) cells by day 9 (middle of linear phase). The initial concentration of IAA (0.08 nanograms per 10(6) cells) rises slowly to a peak of 1.4 nanograms per 10(6) cells by day 9 then decreases rapidly to 0.2 nanograms per 10(6) cells by day 15 (early declining phase) and 0.08 nanograms per 10(6) cells by day 23 (early stationary phase).